Timely Vaccination and Its Associated Factors Among Parents With Children Aged From 0 to 23 Months in Wolaita Zone Public Hospitals, Southern Ethiopia, 2024: A Facility-Based Cross-Sectional Study - Temesgen Geta Hardido MSc; Bizuayehu Atinafu Ataro MSc; Eshetu Elifios MSc (SAGE Publishing, 2024)
Background. This study assessed determinants of timely vaccination among children aged from 0 to 23 months in Wolaita Zone Public hospitals, southern Ethiopia: A facility-based cross-sectional study in the study area. Methods and material. An institution-based cross-sectional study was undertaken in Wolaita Zone Public hospitals from December 12 2023 to January 12 2024, G.C. Study subjects were randomly selected through systematic sampling method. Data were gathered by structured questionnaire, entered into Epidata 4.6 and transferred to SPSS 23 for analysis. An adjusted odds ratio (AOR) along with a 95% confidence interval at a P  < .05 was used to declare significance level. Results. This study found that 71.5% of children were vaccinated timely. Time to reach the health facility, place of delivery, ANC follow-up, attitude, and knowledge of women, significantly attributed to timely vaccination. Conclusion. About 71.5% of study participants vaccinated their children on the national recommended vaccination schedule. Highly strategic interventions should be taken in improving timely vaccination and identified factors.